PENGARUH PENGGUNAAN METODE GUIDED DISCOVERY TERHADAP HASIL BELAJAR IPA SISWA KELAS IV SEKOLAH DASAR - Azizah Azizah; Puji Winarti (Universitas Muhammadiyah Surakarta, 2016)
This study aims to determine the effect of using guided discovery learning method for IPA learningoutcomes. Variables that examined are the learning method that consists of guided learningmethods discovery, conventional method, and student learning outcomes IPA. This research isquasi experimental study. Experimental design to be used in the form pretest-posttest controlgroup design. The population were all fourth grade students in elementary school Gedanganak01 West Ungaran and SD Negeri Langensari 01 West Ungaran. The experiments given classtreatment guided discovery learning method and the control class were given conventionaltreatment methods. Data collection techniques of this study is test to measure student learningoutcomes IPA. Analysis of data using (1) the descriptive statistical techniques to describe thecharacteristics of science learning outcomes; and (2) of inferential statistics by t-test to testthe hypothesis of the study with assisted SPSS 16.0 for Windows. The results showed that thereis significant influence learning method guided discovery to learning outcomes IPA. This wasshown by the differences in learning outcomes in science subjects between learning by usingguided discovery with conventional learning. These results are based on t -.test Gain Score withSig. 0.012 α (0.05).